Private equity challenge - assessment of Calavo growers´ suitability as an Lbo target - Correia, Cristiana Vanessa Lopes (2021)
The following work project was developed by a group of Masters in Finance students and consists on the development of an Investment Committee Paper on Calavo Growers, an American fresh fruit and health yon-the-go fresh food it ems company, in an academical context. The company operates through three segments: Fresh Products–which deals with fresh fruit, mostly avocados; Calavo Foods–that transforms avocados in to processed products, such as guac a mole; and RFG–which hand lesa portfolio of fresh and healthy foods, including fresh-cut fruits. In this segment, the value creation strategy and business plan are presented, which intend to create value for investors during a 7-yeart imehorizon through organic and inorganic growth, consisting of revenue growth, operational improvements, add-on acquisitions and international expansion. This plan is supported by extensive research on the company and on the markets in which it operates.